Klasifikasi Tingkat Kepuasan Siswa Sekolah Dasar Pada Pembelajaran Matematika Berbasis Animasi Menggunakan Algoritma Decision Tree - Alvina Damayanti; Ucok Darmanto Soer; Edora Edora (Journal of Information System Research (JOSH), 2025)
Mathematics learning at SDN Sukamanah 01 shows low student participation due to conventional teaching methods that are predominantly one-way and lack student engagement. To address this, this study specifically evaluates the effectiveness of animation media in improving student learning satisfaction. A total of 500 student response data were analyzed using a Decision Tree algorithm to classify student satisfaction levels towards animation-based learning methods. The classification results show that the majority of students gave positive responses, with 45.6% being in the "very satisfied" category. Specifically, 36 students (7.2%) were very dissatisfied, 46 students (9.2%) were dissatisfied, 52 students (10.4%) were neutral, 138 students (27.6%) were satisfied, and 228 students (45.6%) were very satisfied. The applied Decision Tree model achieved a classification accuracy of 81.33%, indicating that student satisfaction patterns can be systematically identified based on observed attributes such as initial interest in mathematics, classroom interaction, and understanding of the material. These findings confirm that integrating animated media into mathematics learning is effective in enhancing students' overall learning experience, especially in terms of engagement, interest, and positive perceptions of the subject.